Consideration of a recommendation to co-publish optional combinations in alternative classifications of the Ornithogaleae (Scilloideae, Asparagaceae) - Crouch, Neil Robert; Klopper, Ronell R.; Mcneill, John (Phytotaxa, 2014)
A number of new taxa were recently described from the tribe Ornithogaleae of the subfamily Scilloideae in the Asparagaceae, with names following the generic classification by Martínez-Azorín et al. (2011). Manning & Goldblatt (2013) subsequently provided new combinations to enable a transfer of these taxa to an alternative generic classification system proposed by Manning et al. (2009). In view of the prevailing nomenclatural flux within the Ornithogaleae epitomised by the aforementioned publications, Manning & Goldblatt (2013) recommended that “all future descriptions of species and any new combinations in the [Ornithogaleae] include an optional combination in the alternative classification (i.e. Manning et al. 2009 or Martínez-Azorín et al. 2011) to obviate the necessity for separate publications on the combinations, and to facilitate their direct integration into existing collections and databases”.